Characterization of microsatellite loci for an Australian epiphytic orchid, Dendrobium calamiforme, using Illumina sequencing1. (5th June 2015) - Trapnell, Dorset W.; Beasley, Rochelle R.; Lance, Stacey L.; Field, Ashley R.; Jones, Kenneth L.
Abstract : Premise of the study: Microsatellite loci were developed for the epiphytic pencil orchid Dendrobium calamiforme for population genetic and phylogeographic investigation of this Australian taxon. Methods and Results: Nineteen microsatellite loci were identified from an Illumina paired‐end shotgun library of D. calamiforme . Polymorphism and genetic diversity were assessed in 24 individuals from five populations separated by a maximum distance of ∼80 km. All loci were polymorphic with two to 14 alleles per locus, expected heterozygosity ranging from 0.486 to 0.902, and probability of identity values ranging from 0.018 to 0.380. Conclusions: These novel markers will serve as valuable tools for investigation of levels of genetic diversity as well as patterns of gene flow, genetic structure, and phylogeographic history.